STING activation by teniposide: a potential direct mechanism beyond cGAS stimulation - Arranz-Herrero, Javier; Marquez-Cantudo, Laura; Rius-Rocabert, Sergio; Buey, Rubén M.; Velazquez-Campoy, Adrian; Tur-Planells, Vicent; Garcia-Sastre, Adolfo; Miorin, Lisa; de Pascual-Teresa, Beatriz; Coderch, Claire; Nistal-Villan, Estanislao (Frontiers in Immunology, 2026)
IntroductionThe STimulator of Interferon Genes (STING) is a key adaptor protein in the innate immune response to cytosolic DNA, making it a promising therapeutic target. Identifying novel STING ligands could provide new opportunities for immune modulation.MethodsWe employed high-throughput virtual screening to identify potential STING ligands and selected Teniposide, an anticancer drug primarily used for infant leukemia. Direct binding of Teniposide to STING’s cytosolic domain was confirmed via isothermal titration calorimetry (ITC) and validated using a double mutant STING variant unable to bind Teniposide. Computational docking and molecular dynamics simulations were performed to characterize the binding mode.ResultsTeniposide activated the IFN-β signaling pathway in a STING-dependent manner, independent of dsDNA sensors cyclic GMP-AMP synthase (cGAS) and Interferon Gamma Inducible Protein 16 (IFI16). ITC confirmed direct interaction, and the STING double mutant abolished binding. Computational analyses revealed a symmetrical binding mode involving two Teniposide molecules interacting with STING.DiscussionThese findings suggest that Teniposide activates STING through a previously unrecognized, cGAS-independent mechanism, while retaining potential for canonical cGAS-STING stimulation. Our combined computational and experimental evidence supports repurposing Teniposide as a STING agonist, highlighting new therapeutic possibilities for innate immune stimulation.